1997
DOI: 10.1021/ic9611249
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Zero Resistance Temperature above 90 K and Hole Distribution in (Hg0.5Pb0.5)Sr2(Ca0.7Y0.3)Cu2O7-δ via Chemical Substitution of Ba into Sr Sites

Abstract: A significant enhancement of zero resistance temperature [T(c(zero))] from 78 K for x = 0 to 92.5 K for x = 0.2 in the series (Hg(0.5)Pb(0.5))(Sr(2-x)Ba(x))(Ca(0.7)Y(0.3))Cu(2)O(7-delta) compounds has been found. On the basis of the O K-edge X-ray-absorption near-edge structure (XANES) spectra for the series of (Hg(0.5)Pb(0.5))(Sr(2-x)Ba(x))(Ca(0.7)Y(0.3))Cu(2)O(7-delta) samples with x = 0-0.5, the chemical substitution of Ba(2+) for Sr(2+) gives rise to a decrease in the O 2p hole concentration within the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…It can be ascribed to the transition from 3d 9 L → O 1s3d 9 (L denotes a hole on the O 2p x,y orbital) states corresponding to creation of a core hole on the O 1s level and filling of O 2p x,y states admixed to the upper Hubbard band. This transition is strongly related to the hole concentration in CuO 2 and is identical to the corresponding peak discussed above for HgPb-1223/F x [34][35][36][37][38][39][40].…”
Section: Anion Substitution (Fluorine For Oxygen) In Hg-pb-12223 Systemsupporting
confidence: 80%
See 3 more Smart Citations
“…It can be ascribed to the transition from 3d 9 L → O 1s3d 9 (L denotes a hole on the O 2p x,y orbital) states corresponding to creation of a core hole on the O 1s level and filling of O 2p x,y states admixed to the upper Hubbard band. This transition is strongly related to the hole concentration in CuO 2 and is identical to the corresponding peak discussed above for HgPb-1223/F x [34][35][36][37][38][39][40].…”
Section: Anion Substitution (Fluorine For Oxygen) In Hg-pb-12223 Systemsupporting
confidence: 80%
“…The pre-edge peak A at about 528.3 eV is attributed to the transition of O 1s electrons to O 2p holes in the CuO 2 planes from 3d 9 L → O 1s3d 9 (L denotes a hole on the O 2p x,y orbital) states corresponding to the creation of a core hole on the O 1s level and filling of O 2p x,y states located in the CuO 2 planes near the Fermi level. The assignment of this peak to the O 2p xy symmetry rather than the out-of-plane O 2p z symmetry is confirmed by several polarization studies [14,[34][35][36][37]. Chen et al, for example found that the intensity of this pre-edge peak in Tl-2223 decreases with increasing the polarized light's incident angle with the c axis [31].…”
Section: Anion Substitution (Fluorine For Oxygen) In Hg-pb-12223 Systemmentioning
confidence: 68%
See 2 more Smart Citations